Pendidikan Quranic Parenting Pada Anak Usia Dini - Ani Oktarina; Khamim Zarkasih Putro (Jurnal Pendidikan Raudhatul Athfal, 2021)
Parenting the Qur’an is a parenting process based on the values of the Qur'an. The method of article research is library research. Additional data collection obtained from primary data from Sumper, the data collected is analyzed, using the interpretation method, to explain all aspects of the contents of the Koran and focus on the verses of the Koran. The Koran as the holy book of Muslims serves as a guide for humans, including early childhood. Educating children can be achieved by physical and mental efforts. By birth, we can see various tips in educating children and the problems that exist in them. Meanwhile, mentally, we are advised to always pray and ask Allah to be given strength and patience in educating him. For that, never stop praying, because all prayers will be answered. Provide understanding to children about the spiritual values of children from an early age, starting from choosing a life partner, teaching them from the womb, recognizing them when they are born, and guiding them from childhood to adulthood.